Semantic Peculiarities of Homonymy in English and Uzbek (Texas Journal of Philology, Culture and History, 2023)
This article is devoted to the problems of the homonym, its forms, classifications of homonymous words and specific features of these words. Thus, it discusses semantic peculiarities of lexicogrammatical homonymy in English and Uzbek.